Sistem Monitoring Suhu, Kelembaban dan Gas Amonia pada Kandang Sapi Perah Berbasis Teknologi Internet of Things (IOT) - Erlina, Tati (Universitas Andalas, 2017)
In this study, a monitoring system was generated to send data about temperature, humidity, and ammonia gas from a dairy cow cage. This system also provides notifications and recommendation to the owner to carry out certain actions based on data obtained from the dairy cow cage. This system consists of three main components, namely the web server monitoring devices and an application on mobile device. Furthermore, monitoring devices consist of a microcontroller, DHT22 sensor, MQ-135, and ESP266. The microcontroller sends data to the web server and the device moves continuously to notify the state of the dairy cage. From the test results, it is known that the system can send data correctly to mobile devices and web servers. Notification of abnormal conditions is given in an average of 39 seconds.